Potential Combination of Kapok Leaf Extract (Ceiba pentandra G.) and Turmeric Extract (Curcuma domestica Va) as an Anticancer Compound - Muh. Natsir; Sanang Nur Safitri; Oktovia Nurmawati; Muh. Saleh Purnama R.; Ruslan (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2021)
Combination of kapok leaf extract (Ceiba pertandra G.) and turmeric extract (Curcuma domestica Va.) was carried out to determine the potential of extracts in treating cancer with BSLT and murine cells P388. Cancer is a disease that is very feared because it’s difficult to cure, and even rarely causes death. The sample was extracted with methanol, the extract was mixed so that the mixture extract from the two samples was obtained. The results showed that in the BSLT test the mixed extract had a bioactivity against shrimp larvae with an LC50 value of 142.946 ppm. While in Leukemia P388 cell testing showed that the combination of mixed extracts had a cytotoxic effect on Leukemia P388 cancer cells with inhibitory concentration values of 54.34 ppm. This shows that the kapok leaf extract (Ceiba pentandra G.) and combination of turmeric extract (Curcuma domestica Va.) has potential and can be developed as an anticancer agent because it has an IC50 value that can inhibit murine P388 cell growth and LC50 value which can kill shrimp larvae Artemia salina L.